REVERSED PHASE EQUILIBRIUM CONSTRAINTS ON THE STABILITY OF Mg-Fe-Al BIOTITE - Berman R.G.; Aranovich L.Ya.; Rancourt D.G.; Mercier P.H.J. (My University, 2007)
The stability of Mg-Fe-Al biotite has been investigated with reversed phase-equilibrium experiments on four equilibria. Experimental brackets in pure H2O and H2O-CO2 mixtures for the equilibrium: (1) phlogopite + 3 quartz = enstatite + sanidine + H2O are in good agreement with previous experiments in mixed-volatile fluids (Bohlen et al. 1983) and H2O-KCl solutions (Aranovich and Newton 1998), while indicating a reduced stability field for phlogopite compared to previous data in pure H2O (Wood 1976; Peterson and Newton 1989). Aluminum solubility in biotite has been determined in the Fe-, Mg-, and Fe-Mg systems from reversed phase-equilibrium data for the equilibria: (2) 3 eastonite + 6 quartz = 2 phlogopite + 3 sillimanite + sanidine + H2O (3) 3 siderophyllite + 6 quartz = 2 annite + 3 sillimanite + sanidine + H2O over the P-T range ~600-750 °C and 1.1-3.4 kbar. Over the investigated temperatures, the brackets define nominal Al saturation levels of 1.60 ± 0.04 in Mg-biotite, 2.08 ± 0.05 in Fe-biotite, and 1.81 ± 0.03 in biotite with Fe/(Fe + Mg) = 0.43-0.44. The slight decrease in Al with increasing T and decreasing P suggested by the data is less than experimental uncertainties. Compared to biotite on the Phl-Ann join, Al-saturated biotites have a markedly larger stability field, particularly in the Fe-system. This effect has been quantified in the Fe-system with one reversal between 691-709 °C at 2.4 kbar for the equilibrium: (4) biotite + sillimanite + quartz = almandine + sanidine + H2O The combined experimental results place tight constraints on the thermodynamic properties of phlogopite, annite, eastonite, and siderophyllite. The resulting nonzero (ΔH298 = -9.4 kJ/mol, with ΔS = ΔV = 0) energetics for the internal equilibrium: (5) Eastonite + 2/3 Annite = 2/3 Phlogopite + Siderophyllite reflect strong Fe-Al affinity in biotite, which has a marked effect on thermobarometers involving biotite.
Keywords: ANNITE; BIOTITE; EASTONITE; EXPERIMENTAL PETROLOGY; MIXING PROPERTIES; PHASE EQUILIBRIA; PHLOGOPITE; SIDEROPHYLLITE